Heparin-Binding Protein in Bronchoalveolar Lavage Fluid as a Biomarker for Discriminating Severe Bacterial and Viral Pneumonia in Critically Ill Children - Caizhi Huang; Jie Zhang; Cong Zhang; Ping Zhang; Liya Mo (Hindawi Limited, 2023)
Objective. This study is aimed at exploring the ability to use heparin-binding protein (HBP) in bronchoalveolar lavage fluid (BALF) to differentially diagnose bacterial infection from viral infection for severe community-acquired pneumonia (CAP) in critically ill children. Methods. A total of 181 children with severe CAP admitted to the intensive care unit (ICU) were included in this study. BALF and blood samples were collected within the first 24 hours of admission. BALF HBP and interleukin-6 (IL-6) concentrations and neutrophil percentage (N%) as well as blood HBP, IL-6, procalcitonin (PCT), C-reactive protein, white blood cell concentrations and N% were measured. Results. Of the enrolled children, 126 were confirmed to have bacterial pneumonia, and 55 were confirmed to have viral pneumonia. Blood HBP and PCT concentrations and N% and BALF HBP and IL-6 concentrations and N% were significantly higher in bacterial pneumonia than in viral pneumonia (P<0.05). In the bacterial pneumonia group, HBP and IL-6 concentrations and N% in BALF samples were all significantly higher than those in blood samples (P<0.001), and BALF HBP and IL-6 concentrations and N% were correlated with blood HBP and IL-6 concentrations and N%, respectively (r=0.439, 0.250, and 0.235, P<0.01). BALF N% and blood N% were both correlated with BALF HBP concentrations and blood HBP concentrations, respectively (r=0.622 and 0.346, P<0.001). ROC analysis revealed that BALF HBP showed the best ability to predict bacterial pneumonia, with an area under the curve of 0.994, a sensitivity of 95.24%, and a specificity of 100.00% at its optimal cutoff value of 74.05 ng/mL. Conclusion. BALF HBP might be a promising biomarker for the early discrimination of bacterial infection from viral infection in critically ill children with severe CAP.